An Observational Study on Tolerability and Safety of Cisplatin Chemotherapy in Various Cancer - Andhi, Nikhilesh; Sravya, Aluru; Praneetha, Sate; Raghavi, Sri Romoju Govinda; Kusuma, Kancharla (Journal of Pharmacy Practice and Community Medicine)
Aim: To find out the safety and tolerability of cisplatin either given as individual therapy or in combination with other anticancer drugs or with radiotherapy. Materials and Methods: A prospective observational study was conducted in the oncology department (inpatient) of tertiary care hospital. The data was collected from the in-patient department after considering inclusion and exclusion criteria for a period of 6 months. Safety was analyzed using EORTC scales and Tolerability was assessed by collecting the laboratory data every week of the therapy. Statistical tools like Chi-square test were applied to the data by using SPSS software. Results: A total of 107 cancer patients, female patients predominated over males. Most common age group were under of 51-60 years. All the patients in our study were treated with cisplatin in combination with radiotherapy than monotherapy or in combination with other anticancer drugs. Higher incidence of tongue cancer cases were reported followed by less number of anal cancer cases. The quality of life and the functioning ability of cancer patients are calculated via EORTC scale. The QOL is highest in esophageal cancer patients and the lowest in cervical cancer patients. The social functioning of the subjects is very good in every cancer whereas the physical functioning is decreased in anal and buccal cancer patients. The cisplatin is given in the combination with radiotherapy for a total of 6 weeks. Every week after the therapy, the blood samples were collected and the toxicities are checked. Nausea and vomiting, fatigue, loss of appetite, insomnia are the side effects seen during the therapy. Few cases of Hematological toxicities like reduction in Hb count, PCV, lymphocyte count and increase in Neutrophil count were seen. By this, we can say that cisplatin is well tolerated and is safe in the chemotherapy with minimal side effects. Conclusion: Cisplatin is well tolerated in adults who are diagnosed with various cancers with minimal side effects which were controlled with supportive therapy. Whereas no serious ADRs reported in the study and no recurrence of the disease was observed. Thus, cisplatin is beneficial in the treatment of various cancers as it is safe and well tolerated.
Keywords: Cisplatin; ADR; Re-occurrence; Hb; PCV; Safety and tolerability; Various cancers; EORTC scale